The effects of sprout-damaged milo on finishing pig performance - Goodband, Robert D.; Turlington, W.H.; Hines, Robert H.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and sixty-five, crossbred, growing-finishing pigs were utilized in two growth trials to determine the effects of sprout-damaged milo on pig performance. Sprout-damaged milo was officially graded as having 39% sprout damage and 10% broken kernels. In addition, the grain was badly weathered and discolored. In Trial 1, sprout-damaged milo was substituted for normal milo at levels of 0, 50, and 100% of the grain portion in the diet. Increasing levels of sprout-damaged milo had no effect (P>.20) on average daily gain (ADG) or average daily feed intake (ADFI) of growing pigs (91 to 145 lbs). However, pigs fed the 50 and 100% sprout-damaged milo had numerically poorer feed efficiency (8 and 11%, P>.20) than those fed the normal milo diet. In Trial 2, sprout-damaged milo replaced 0, 25, 50, 75 or 100% of the normal milo in the diet. Increasing levels of sprout-damaged milo had no effect on ADG, ADFI, or feed efficiency (F/G; P>.30) of growing-finishing pigs. These results indicate that milo with up to 40% sprout damage may be utilized in growing-finishing pig diets without adversely affecting pig performance.
Keywords: Swine; Spout-damaged milo; Finishing pig; Performance